PHILOSOPHICAL REFLECTION ON THE ROLE AND SIGNIFICANCE OF SPORT IN SOCIETY - Azimov, Sherzod (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2023)
The article examines the socio-philosophical aspect of sport and its humanistic potential in modern society. The author draws attention to the aesthetic, philosophical and ideological significance of sport, as well as its role in the formation of basic structures, norms, values and ideals of public consciousness. The article examines the pragmatic philosophy and ideas of Dewey, which focus on the importance of sports in the education and upbringing of the individual.